Development of a shared decision-making tool to assist patients and clinicians with decisions on oral anticoagulant treatment for atrial fibrillation. (2nd December 2015) - Kaiser, Karen; Cheng, Wendy Y.; Jensen, Sally; Clayman, Marla L.; Thappa, Andrew; Schwiep, Frances; Chawla, Anita; Goldberger, Jeffrey J.; Col, Nananda; Schein, Jeff
Abstract: Objective: Decision aids (DAs) are increasingly used to operationalize shared decision-making (SDM) but their development is not often described. Decisions about oral anticoagulants (OACs) for atrial fibrillation (AF) involve a trade-off between lowering stroke risk and increasing OAC-associated bleeding risk, and consideration of how treatment affects lifestyle. The benefits and risks of OACs hinge upon a patient's risk factors for stroke and bleeding and how they value these outcomes. We present the development of a DA about AF that estimates patients' risks for stroke and bleeding and assesses their preferences for outcomes. Research design and methods: Based on a literature review and expert discussions, we identified stroke and major bleeding risk prediction models and embedded them into risk assessment modules. We identified the most important factors in choosing OAC treatment (warfarin used as the default reference OAC) through focus group discussions with AF patients who had used warfarin and clinician interviews. We then designed preference assessment and introductory modules accordingly. We integrated these modules into a prototype AF SDM tool and evaluated its usability through interviews. Results: Our tool included four modules: (1) introduction to AF and OAC treatment risks and benefits; (2) stroke risk assessment; (3) bleeding risk assessment; and (4) preference assessment. Interactive risk calculators estimated patient-specific stroke and bleeding risks; graphics were developed to communicate these risks. After cognitive interviews, the content was improved. The final AF tool calculates patient-specific risks and benefits of OAC treatment and couples these estimates with patient preferences to improve clinical decision-making. Conclusions: The AF SDM tool may help patients choose whether OAC treatment is best for them and represents a patient-centered, integrative approach to educate patients on the benefits and risks of OAC treatment. Future research is needed to evaluate this tool in a real-world setting. The development process presented can be applied to similar SDM tools.